ANALISIS TAX PLANNING UNTUK EFISIENSI PAJAK PENGHASILAN (PPh ) PASAL 21 PADA PT. TRINITY SUKSES - Sumual, Laura; Elim, Inggriani; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Income tax is a tax collected on the tax object on his income. The purpose of the government that intends to maximize revenue from the tax sector is in fact contrary to the objectives of tax payers, where taxpayers try to streamline their tax burden so as to obtain greater profits in order to prosper their owners and continue the survival of their companies. Done by the company, one of which is by planning income tax especially Income Tax 21. The purpose of this study is to analyze the application of tax planning to corporate income tax, whether it is in accordance with the regulation of the Director General of Tax Number PER-31 /PJj / 2009 and Llaw no. 36 of 2008, and how the company utilizes tax regulations for planning taxes on corporate income tax. Objects that are subject to income tax are income from a person for work or business, agency or business form. This research is a descriptive study that compares and describes the state of an object of research in this case PT. Trinity sukses manado, by processing data and then comparing the results with the theory obtained. The results of this study are that the company has not carried out tax planning efficiently.